Prostate deformation during hypofractionated radiotherapy: an analysis of implanted fiducial marker displacement - Knybel, Lukas; Cvek, Jakub; Blazek, Tomas; Binarova, Andrea; Parackova, Tereza; Resova, Kamila (Radiation oncology, 2021)
BACKGROUND: To report prostate deformation during treatment, based on an analysis of fiducial marker positional differences in a large sample. MATERIAL AND METHODS: This study included 144 patients treated with prostate stereotactic body radiation therapy after implantation in each of 4 gold fiducial markers (FMs), which were located and numbered consistently. The center of mass of the FMs was recorded for every pair of X-ray images taken during treatment. The distance between each pair of fiducials in the live X-ray images is calculated and compared with the respective distances as determined in the CT volume. The RBE is the difference between these distances. Mean RBE and intrafraction and interfraction RBE were evaluated. The intrafraction and intefraction RBE variability were defined as the standard deviation, respectively, of all RBE during 1 treatment fraction and of the mean daily RBE over the whole treatment course. RESULTS: We analyzed 720 treatment fractions comprising 24,453 orthogonal X-ray image acquisitions. We observed a trend to higher RBE related to FM4 (apex) during treatment. The fiducial marker in the prostate apex could not be used in 16% of observations, in which RBE was > 2.5 mm. The mean RBEavg was 0.93 ± 0.39 mm (range 0.32-1.79 mm) over the 5 fractions. The RBEavg was significantly lower for the first and second fraction compared with the others (P < .001). The interfraction variability of RBEavg was 0.26 ± 0.16 mm (range 0.04-0.74 mm). The mean intrafraction variability of all FMs was 0.45 ± 0.25 mm. The highest Pearson correlation coefficient was observed between FM2 and FM3 (middle left and right prostate) (R = 0.78; P < .001). Every combination with FM4 yielded lower coefficients (range 0.66-0.71; P < .001), indicating different deformation of the prostate apex. CONCLUSIONS: Ideally, prostate deformation is generally small, but it is very sensitive to rectal and bladder filling. We observed RBE up to 11.3 mm. The overall correlation between FMs was affected by shifts of individual fiducials, indicating that the prostate is not a "rigid" organ. Systematic change of RBE average between subsequent fractions indicates a systematic change in prostate shape.
Keywords: Radiotherapy, Image-Guided; pohyb; Tomography, X-Ray Computed; počítačové zpracování obrazu; Radiotherapy Dosage; celková dávka radioterapie; zaměřovací značky pro radioterapii; mužské pohlaví; nádory prostaty; Fiducial Markers; Radiation Dose Hypofractionation; Radiotherapy, Intensity-Modulated; radioterapie řízená obrazem; Prostatic Neoplasms; Humans; hypofrakcionace při ozařování; radioterapie s modulovanou intenzitou; Movement; plánování radioterapie pomocí počítače; Image Processing, Computer-Assisted; Prostheses and Implants; počítačová rentgenová tomografie; lidé; Male; protézy a implantáty; Radiotherapy Planning, Computer-Assisted